PENGEMBANGAN MEDIA POWER POINT SEBAGAI MEDIA PEMBELAJARAN BUDAYA MELAYU RIAU KELAS II SDN 182 PEKANBARU - Karmila; Febrina Dafit (STKIP Subang, 2023)
This research aims to develop power point media as a medium for learning Riau Malay culture for class II at SDN 182 Pekanbaru. This research uses a research development or R&D approach which includes several stages, namely the analysis stage, design stage, development stage, implementation stage. Data was collected through interviews and questionnaires on the power point media that was developed. This research is expected to have a positive influence on the development of creative and innovative learning methods, especially in the context of Riau Malay cultural learning. Apart from that, it is also hoped that it can become a reference for schools and teachers in choosing appropriate learning media for each lesson.